Blessed Edmund Campion - Guiney, Louise Imogen, 1861-1920; Durden, James, 1878-1964; Smart, John (Salt Lake City, UT : Project Gutenberg, 2016)
"Blessed Edmund Campion" by Louise Imogen Guiney is a historical account written in the early 20th century. The book depicts the life of Edmund Campion, a prominent Jesuit and martyr during the tumultuous religious landscape of sixteenth-century England. It chronicles his journey from his early Catholic upbringing through his intellectual pursuits, challenges of faith, and ultimately his commitment to the Catholic Church amid persecution. The opening of this work introduces readers to Campion's youth in London and Oxford during the mid-1500s. It highlights the influences that shaped his early life, including his Catholic upbringing and academic achievements, which earned him a respected position at Oxford. However, as the Protestant Reformation surged under Queen Elizabeth I, Campion grappled with his faith amidst increasing turmoil and societal pressures, foreshadowing the significant inner conflict that would drive his eventual decision to dedicate himself fully to the Catholic cause. This part of the narrative sets the stage for Campion's deepening spiritual journey and the looming challenges he would face as he chose fidelity to his beliefs over personal safety and ambition. (This is an automatically generated summary.)
Release date is 2016-08-05
E-text prepared by Emmy, MWS, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Campion, Edmund, Saint, 1540-1581; Jesuits -- England; Christian martyrs -- Great Britain -- Biography